Prevalence and correlates of HCV monoinfection and HIV and HCV coinfection among persons who inject drugs in Vietnam. Issue 5 (May 2015) - Zhang, Long; Celentano, David D.; Le Minh, Nguyen; Latkin, Carl A.; Mehta, Shruti H.; Frangakis, Constantine; Ha, Tran Viet; Mo, Tran Thi; Sripaipan, Teerada; Davis, Wendy W.; Quan, Vu Minh; Go, Vivian F.
Abstract : Background: Vietnam bears a high burden of hepatitis C virus (HCV) and HIV infection among persons who inject drugs (PWID). The high prevalence of HCV and HIV occurs in a context of stigma and limited preventive interventions for PWID. Objectives: This study aims to estimate the prevalence of HCV, HIV, and HIV/HCV coinfection among PWID and to explore their associations with lifetime injection behaviors. Methods: A total of 1434 PWID were recruited from the Thai Nguyen Province of Vietnam between 2005 and 2007. Participants responded to a structured questionnaire and provided blood samples at baseline. A cross-sectional analysis of data collected at baseline was carried out. Factors associated with HCV monoinfection and HIV/HCV coinfection were evaluated by multinomial logistic regression. Results: The prevalences of HIV and HCV were 35.1 and 88.8%, respectively, and the prevalences of HIV/HCV coinfection and HCV monoinfection were 34.8 and 53.9%, respectively. After adjusting for confounders in multivariate analysis, ever reusing a syringe and needle was found to be significantly associated with HIV monoinfection [adjusted odds ratio (AOR), 3.13; 95% confidence interval (CI), 1.99–4.94] and HIV/HCV coinfection (AOR, 3.34; 95% CI, 2.02–5.51). Ever sharing diazepam or novocaine was also found to be significantly associated with HIV monoinfection (AOR, 2.14; 95% CI, 1.38–3.32) and HIV/HCV coinfection (AOR, 2.47; 95% CI, 1.57–3.90). Conclusion: Our findings demonstrate a high burden of HIV and HCV infection among PWID in Vietnam. Lifetime injection behaviors, including sharing of diazepam or novocaine, may account for the high prevalence of HIV and HCV. Improving prevention and ensuring access to care remain critically important for this vulnerable population.